Rapid pressureless sintering preparation method of broadband high-transparency AlON ceramic
By preparing the mixing of nano Y2O3 powder with cluster characteristics and AlON powder, using its uniform distribution and densification ability in AlON ceramics, the problems of unsatisfactory microstructure and difficulty in discharge of pores during sintering are solved, and the problem of unsatisfactory microstructure during sintering is achieved. Fast pressure-free sintering to prepare wide band high-transmittance AlON ceramics, which have the advantages of high transmittance and hardness.
Patent Information
- Application Number
- CN202411602146.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-11
AI Technical Summary
During the pressure-free sintering preparation of AlON transparent ceramics, the microstructure in the early and mid-stage sintering is not ideal, resulting in difficulty in discharge of pores in the late sintering and requires long-term high-temperature insulation to achieve high light transmission.
The porous precursors were prepared by yttrium nitrate, citric acid and ethylene glycol to obtain nano Y2O3 powder with cluster characteristics, mixed with AlON powder, and sintered without pressure under a nitrogen atmosphere, and uniform distribution and density of cluster Y2O3 were used. The chemical capacity controls the sintering process and promotes efficient discharge of pores.
It realizes the preparation of wide band high-transmittance AlON ceramics in a short insulation time, which reduces the sintering temperature and time, improves efficiency and cost-effectiveness, and has high transmittance and hardness.
Smart Images

Figure HDA0005128587920000011 
Figure HDA0005128587920000012 
Figure HDA0005128587920000021
Abstract
Description
Technical Field
[0001] The invention relates to a rapid pressureless sintering preparation method of wide-band high-light-transmittance AlON ceramics, belonging to the field of transparent ceramic material preparation. Background Art
[0002] AlON (aluminum oxynitride) transparent ceramics have a cubic spinel structure and are optically isotropic. They have the advantages of high light transmittance and good mechanical properties. They are one of the most promising structural-functional integrated transparent ceramic window materials and can be widely used in transparent armor, infrared detection, protective windows and other fields. They have broad application prospects in national defense security and civilian fields.
[0003] Among the many ceramic sintering methods, pressureless sintering has the advantages of easy equipment availability and low cost, and has unique advantages in product size enlargement. Therefore, under the premise of ensuring product performance, pressureless sintering has become the preferred method for sintering and preparing ceramic materials. Similarly, for the preparation of AlON transparent ceramics, people also expect to obtain AlON ceramics with excellent light transmittance only by pressureless sintering. However, in the process of preparing ceramics by sintering AlON powder, AlON can first decompose to form α-Al2O3 (aluminum oxide) and AlN (aluminum nitride), and then reform AlON under higher temperature conditions. This process is affected by the coupling of multiple factors such as AlON powder particle size, sintering aids and their dosage. These effects may lead to problems such as unsatisfactory microstructures formed in the early and middle stages of sintering and insufficient sintering driving force in the later stages of sintering, which in turn leads to the abnormal difficulty of pore discharge in the high-densification sintering stage in the later stages of sintering. Therefore, the pressureless sintering preparation of AlON transparent ceramics often requires keeping warm at high temperature (1880-2000℃) for 7-30h to effectively expel the pores and obtain better light transmittance.
[0004] It can be seen that in order to efficiently discharge pores and achieve rapid preparation of highly translucent AlON ceramics, it is necessary to control the decomposition degree of AlON in the early and middle stages of sintering to avoid particle agglomeration / coarsening caused by excessive α-Al2O3, and to ensure that there is still sufficient sintering driving force in the later stage of sintering to promote the effective discharge of small pores in a shorter holding time. Therefore, regulating the particle size of sintering aids and AlON powders, and controlling the phase transformation and microstructure evolution of the entire sintering process through the synergistic effect of the two, and further using sintering aids to provide sufficient driving force for the later high-densification sintering on the premise of ensuring a good microstructure in the early and middle stages of sintering, should be an effective way to obtain high-density and high-transmittance AlON ceramics. Summary of the invention
[0005] The object of the present invention is to provide a rapid pressureless sintering preparation method of wide-band high-transmittance AlON ceramics, specifically, using yttrium nitrate, citric acid and ethylene glycol to first prepare a porous precursor, then calcining to obtain a nano Y2O3 powder with cluster characteristics, then mixing the obtained Y2O3 powder with AlON powder, and using a pressureless sintering method to prepare a wide-band high-transmittance AlON ceramics under nitrogen atmosphere conditions. The nano Y2O3 powder with cluster characteristics can be evenly distributed in the AlON powder as a whole to avoid local excessive enrichment, and prevent AlON from decomposing in large quantities to produce excessive α-Al2O3 in the early and middle stages of sintering, so that the ceramics have a better microstructure before entering the late stage of sintering, and the clustered Y2O3 can also be used to ensure that the ceramics have a sufficient concentration of Y that can promote sintering densification, so that the late stage of sintering still has the ability to densify and sinter, and promote the efficient discharge of small-sized pores. Therefore, in the later heat preservation stage, the pores are continuously discharged, thereby realizing the rapid pressureless sintering preparation of AlON ceramics with high light transmittance in a wide band. This method has short high-temperature heat preservation time, high efficiency, good energy-saving effect, low cost, simple operation process, and easy to achieve large-scale production.
[0006] A rapid pressureless sintering preparation method for wide-band high-transmittance AlON ceramics, comprising: ball-milling and mixing Y2O3 raw material powder and AlON raw material powder, drying and granulating to obtain AlON / Y2O3 mixed powder; then unidirectionally press-forming the AlON / Y2O3 mixed powder, and then cold isostatically pressing to obtain a green body; finally, pressurelessly sintering the green body in a nitrogen atmosphere to obtain wide-band high-transmittance AlON transparent ceramics, wherein:
[0007] The Y2O3 powder in the AlON / Y2O3 mixed powder is uniformly distributed in the mixed powder in the form of single particles and clusters consisting of 2 to 5 and 6 to 60 single particles. The mass of the Y2O3 powder in the cluster form consisting of 6 to 60 single particles is 50% to 80% of the Y2O3 raw material powder.
[0008] In the method of the present invention, the Y2O3 powder in the AlON / Y2O3 mixed powder exists in the form of a single particle, a small cluster consisting of 2 to 5 single particles, and a large cluster consisting of 6 to 60 single particles, wherein:
[0009] The mass of the Y2O3 powder in the form of large clusters consisting of 6 to 60 single particles is 50% to 80% of the Y2O3 raw material powder.
[0010] In the method described in the present invention, different forms of Y2O3 powder are uniformly distributed in the AlON / Y2O3 mixed powder as a whole, which can limit the degree of AlON decomposition in the early and middle stages of sintering and control the α-Al2O3 content in the sample at a low level, thereby preventing particle agglomeration / coarsening before entering the late stage of sintering.
[0011] In the method described in the present invention, the Y2O3 powder in the form of large clusters composed of 6 to 60 single particles can ensure that the ceramic has a sufficient concentration of yttrium (Y) to promote sintering densification, so that the pores of AlON can still be efficiently discharged in the later stage of sintering, thereby realizing the preparation of wide-band high-transmittance AlON ceramics through pressureless sintering under shorter insulation time conditions.
[0012] In the method of the present invention, the primary particle size of the Y2O3 raw material powder is 20 to 100 nm, the primary average particle size is 30 to 70 nm, and the specific surface area is 20 to 30 m 2 / g.
[0013] In the method described in the present invention, the Y2O3 raw material powder can be first ball-milled in anhydrous ethanol at a speed of 150-180 rpm for 8-14 hours using silicon nitride balls with a diameter of 3-5 mm and then mixed with AlON powder, wherein the ball-to-material ratio of the ball-milled Y2O3 raw material powder is 8-11:1.
[0014] In the method of the present invention, the Y2O3 raw material powder can be prepared by the following method:
[0015] S1: Weigh yttrium nitrate and citric acid in a molar ratio of 1:3, add 50 mL of deionized water, and stir to dissolve until a transparent solution is formed;
[0016] S2: Weigh ethylene glycol in a molar ratio of 3:1 between citric acid and ethylene glycol, add it to the transparent solution obtained in S1, heat it to 70-90°C in an oil bath, and continue stirring until a viscous sol is formed;
[0017] S3: The viscous sol obtained in S2 is kept in an oven at 70-90°C for 20-26 hours to form a gel;
[0018] S4: heating the gel obtained in S3 to 220-250°C in a muffle furnace at a rate of 5-30°C / min and maintaining the temperature for 1-4 hours to foam and form a porous precursor;
[0019] S5: Grind the porous precursor, pass it through a 50-mesh sieve, heat it to 850-950°C in a muffle furnace at a rate of 10-20°C / min and keep it at that temperature for 1-4 hours to obtain pure Y2O3 powder.
[0020] Furthermore, the purity of the yttrium nitrate is ≥99.99%, the purity of the citric acid is ≥99.5%, and the purity of the ethylene glycol is ≥99%.
[0021] In the method of the present invention, the Y2O3 raw material powder and the AlON raw material powder are first ball-milled at 150-180 rpm for 12-14 h, and then ball-milled at 180-240 rpm for 16-20 h to obtain AlON / Y2O3 mixed powder.
[0022] Furthermore, the dosage of the Y2O3 raw material powder is 0.2-0.4% of the mass of the AlON raw material powder.
[0023] Furthermore, the D of the obtained AlON / Y2O3 mixed powder 50 The particle size distribution range is 0.8~1.4μm and 0.05~8.0μm.
[0024] The ball milling operation described in the present invention is carried out in a device provided by the prior art, preferably a planetary ball mill.
[0025] In the method of the present invention, the unidirectional pressure preforming is completed at 30-60 MPa, and the cold isostatic pressing is completed at 100-180 MPa.
[0026] In the method of the present invention, the heating rate of the pressureless sintering is 10-30°C / min, the sintering temperature is 1860-1900°C, and the holding time is 3.5-5.5h.
[0027] A preferred technical solution of the present invention:
[0028] ① Preparation of nano Y2O3 raw material powder: weigh yttrium nitrate and citric acid, add deionized water, stir and dissolve to form a transparent solution; add ethylene glycol, heat in an oil bath, and continue to stir to form a viscous sol; keep warm in an oven to form a gel; then calcine in a muffle furnace to foam to form a porous precursor; grind the porous precursor, sieve, and continue to calcine in a muffle furnace to obtain pure phase Y2O3 powder;
[0029] ② Raw material mixing: ball-mill the Y2O3 raw material powder obtained in step ①, then weigh the AlON powder and the Y2O3 powder obtained after ball milling, place the two in a ball mill, and ball-mill them in anhydrous ethanol using silicon nitride balls as grinding media to obtain slurry, and then dry and granulate to obtain AlON / Y2O3 mixed powder;
[0030] ③ Green body forming: The AlON / Y2O3 mixed powder obtained in step ② is first preformed by unidirectional pressure, and then cold isostatically pressed to obtain a green body;
[0031] ④ Pressureless sintering: The green body obtained in step ③ is placed in a vacuum atmosphere graphite furnace, and pressureless sintering is performed in a nitrogen atmosphere to prepare AlON transparent ceramics.
[0032] Preferably, the rapid pressureless sintering preparation method of the AlON transparent ceramic with wide-band high light transmittance comprises a post-processing step: grinding and polishing the transparent ceramic obtained in step ④.
[0033] Another object of the present invention is to provide AlON transparent ceramics prepared by the above method.
[0034] The AlON transparent ceramic obtained by the invention has a transmittance of ≥80% in the wavelength range of 350-4480nm, a maximum transmittance of 87.5%, a transmittance of 81.2% at 400nm, and HV>17GPa.
[0035] Beneficial effects of the present invention: by preparing nano Y2O3 powder with certain cluster characteristics, and using it as a sintering aid to prepare AlON transparent ceramics, while achieving overall uniform distribution of Y2O3, clustered Y2O3 is used to make the ceramics still have good densification sintering ability in the later stage of sintering. On the one hand, the overall uniform distribution of Y2O3 (avoiding excessive local Y concentration) can limit the degree of AlON decomposition in the early and middle stages of sintering, and control the α-Al2O3 content in the sample at a low level, thereby preventing particle agglomeration / coarsening before entering the later stage of sintering. On the other hand, the clustered Y2O3 particles can ensure that the ceramic has a sufficient concentration of Y that can promote sintering densification, so that the pores of AlON can still be efficiently discharged in the later stage of sintering, thereby realizing the preparation of wide-band high-transmittance AlON ceramics through pressureless sintering under a shorter insulation time. The ceramic preparation process of the present invention has a short insulation time, and the ceramic obtained by insulation for 4 hours has the advantages of a wide range of high-transmittance wavelengths and high transmittance. The ceramics prepared by the present invention have a transmittance of ≥80% in the 350-4480nm band, a maximum transmittance of 87.5%, and a transmittance of 81.2% at 400nm. In addition, the ceramics also have the characteristics of high hardness, HV>17GPa. The preparation process of the Y2O3 powder with cluster characteristics in the present invention is simple and low in cost; the pressureless sintering technology equipment is easy to obtain and the investment cost is low; the sintering process has a short insulation time, good energy-saving effect, high efficiency, low preparation cost, and easy to realize industrialization; the prepared ceramics have a wide wave transmission range, good light transmittance, and broader application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 (a) is the XRD spectrum of the Y2O3 powder obtained in Example 1, and the Y2O3 powder used in Comparative Example 1 and Comparative Example 2; Figure 1 (b) is the SEM image of the Y2O3 powder obtained in Example 1; Figure 1 (c) is the SEM image of the Y2O3 powder used in Comparative Example 1; Figure 1 (d) is the SEM image of the Y2O3 powder used in Comparative Example 2.
[0037] Figure 2This is the TEM image of the Y2O3 powder obtained in Example 1.
[0038] Figure 3 (a) and (b) are the SEM images and EDS distribution diagrams of the Y element of the AlON / Y2O3 mixed powder after ball milling in Example 1; Figure 3 (c) and (d) are the SEM images and EDS distribution diagrams of the Y element of the AlON / Y2O3 mixed powder after ball milling in Comparative Example 1; Figure 3 (e) and (f) are the SEM images and EDS distribution diagrams of the Y element of the AlON / Y2O3 mixed powder after ball milling in Comparative Example 2.
[0039] Figure 4 Graph showing the transmittance of AlON transparent ceramics obtained in Example 1, Comparative Example 1 and Comparative Example 2.
[0040] Figure 5 The fracture morphologies of the AlON transparent ceramics obtained in Example 1(a), Comparative Example 1(b) and Comparative Example 2(c) are shown.
[0041] Figure 6 This is a graph showing the change in α-Al2O3 content during the heating process of the AlON transparent ceramics obtained in Example 1, Comparative Example 1 and Comparative Example 2.
[0042] Figure 7 This is a diagram of the microstructure evolution process of the AlON transparent ceramics obtained in Example 1, Comparative Example 1 and Comparative Example 2 during the heating process.
[0043] Figure 8 This is a densification process curve diagram of the AlON transparent ceramics obtained in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0044] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0045] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0046] One of the specific implementations:
[0047] ① Preparation of nano Y2O3 raw material powder:
[0048] S1: Weigh yttrium nitrate and citric acid in a molar ratio of 1:3, add 50 mL of deionized water, and stir to dissolve until a transparent solution is formed;
[0049] S2: Weigh ethylene glycol in a molar ratio of 3:1 between citric acid and ethylene glycol, add it to the transparent solution obtained in S1, heat it to 70-90°C in an oil bath, and continue stirring until a viscous sol is formed;
[0050] S3: The viscous sol obtained in S2 is kept in an oven at 70-90°C for 20-26 hours to form a gel;
[0051] S4: heating the gel obtained in S3 to 220-250°C in a muffle furnace at a rate of 5-30°C / min and maintaining the temperature for 1-4 hours to foam and form a porous precursor;
[0052] S5: Grind the porous precursor, pass it through a 50-mesh sieve, and heat it to 850-950°C in a muffle furnace at a rate of 10-20°C / min and keep it for 1-4h to obtain pure Y2O3 powder;
[0053] ② Raw material mixing: The Y2O3 raw material powder obtained in step (1) is ball-milled in anhydrous ethanol at a speed of 150-180 rpm for 8-14 h using silicon nitride balls with a diameter of 3-5 mm to obtain ball-milled Y2O3 powder, wherein the ball-to-material ratio of the ball-milled Y2O3 raw material powder is 8-11:1; then AlON powder and the ball-milled Y2O3 powder obtained in the above step are weighed, wherein the Y2O3 powder dosage is 0.2-0.4% of the mass of the AlON powder, and the two are placed in a ball mill, and ball-milled in anhydrous ethanol at 150-180 rpm for 12-14 h using silicon nitride balls as a grinding medium, and then continued to ball-mill at 180-240 rpm for 16-20 h to obtain a slurry, and after drying and granulation, an AlON / Y2O3 mixed powder is obtained;
[0054] ③ Green body molding: The AlON / Y2O3 mixed powder obtained in step (2) is first preformed by uniaxial pressing at 30-60 MPa, and then cold isostatic pressing at 100-180 MPa to obtain a green body;
[0055] ④ Pressureless sintering: Place the green body obtained in step (3) into a vacuum atmosphere graphite furnace, heat it to 1860-1900° C. at a rate of 10-30° C. / min under a nitrogen atmosphere, and keep it at that temperature for 3.5-5.5 hours to prepare AlON transparent ceramics by pressureless sintering;
[0056] ⑤Processing: Grind and polish the AlON transparent ceramics.
[0057] Example 1
[0058] A rapid pressureless sintering preparation method for wide-band high-transmittance AlON ceramics
[0059] First, weigh 3.8301g of yttrium nitrate (purity of 99.99%) and 5.7636g of citric acid (purity of 99.5%), add 50mL of deionized water, and stir to form a transparent solution; then add 0.62g of ethylene glycol (purity of 99%), heat the resulting solution to 80°C in an oil bath, and continue stirring to form a viscous sol; then continue to keep it at 80°C in an oven for 24h to form a gel; transfer the gel to a muffle furnace, heat it to 240°C at 10°C / min and keep it for 2h, and form a porous precursor through foaming; grind the porous precursor, pass it through a 50-mesh sieve, and place it in a muffle furnace, heat it to 900°C at 10°C / min and keep it for 2h to obtain Y2O3 raw material powder.
[0060] The phase composition and microstructure of the prepared Y2O3 raw material powder are shown in Figure 1 (a), (b) and Figure 2 , indicating that pure phase Y2O3 powder was obtained. The primary particle size of the powder was granular, and multiple particles formed clusters.
[0061] The Y2O3 powder obtained above was ball milled at 170 rpm for 12 h in a planetary ball mill. The grinding balls used were silicon nitride balls with a diameter of 4 mm, and the ball-to-material ratio was 10:1. The primary particle size of the Y2O3 powder after ball milling was 20-100 nm, the average particle size was 51 nm, and the specific surface area was 25 m 2 / g.
[0062] Weigh AlON powder and the Y2O3 powder after ball milling, wherein the Y2O3 content is 0.3wt.%, and use silicon nitride balls as grinding medium to first ball mill at 170rpm for 12h in anhydrous ethanol, then increase the speed to 210rpm and continue ball milling for 18h. The morphology and Y element distribution of the AlON / Y2O3 powder obtained after ball milling are shown in Figure 3 (a) and (b), it can be seen that the different forms of Y2O3 powder are distributed uniformly in the mixed powder, and Y2O3 clusters consisting of about 40 Y2O3 single particles can be observed. In the AlON / Y2O3 powder obtained after ball milling, the mass of Y2O3 clusters consisting of 6 to 60 single particles accounts for 64% of the mass of Y2O3 raw material powder.
[0063] The ball-milled AlON / Y2O3 mixed powder was preformed at 50MPa for 5 minutes, and then cold isostatically pressed at 120MPa to obtain a green body; the green body was placed in a graphite furnace, heated to 1880℃ at 15℃ / min in a nitrogen environment, and kept warm for 4 hours to obtain AlON transparent ceramics. The prepared AlON transparent ceramics were double-sided ground and polished to 2mm thickness to measure the transmittance. Figure 4This is the transmittance curve of the prepared AlON transparent ceramic. It can be seen that the prepared AlON ceramic has good light transmittance. The transmittance is ≥80% in the wide band range of 350 to 4480 nm, the maximum transmittance is 87.5% (3600 nm), and the transmittance at 400 nm is 81.2%. Figure 5 (a) is the fracture morphology of the prepared AlON transparent ceramics. It can be seen that the prepared AlON transparent ceramics have no obvious pores. Figure 6 This is a graph showing the change in α-Al2O3 content during the heating process. It can be seen that the α-Al2O3 content produced by the decomposition of AlON is maintained at a low level (22wt.%). Figure 7 This is a diagram of the fracture morphology changes during the heating process. It can be seen that there is no obvious particle agglomeration / coarsening phenomenon in the ceramic during the heating process. Figure 8 The densification process curve shows that the ceramic has a good densification effect during the heating process, and the relative density of the ceramic after heat preservation sintering reaches 99.85%.
[0064] Comparative Example 1
[0065] Comparative Example 1 The method of Example 1 was followed, except that the average particle size of nano Y2O3 was 30.4 nm and the particles were in a soft agglomerated state (see Figure 1 (a) and (c)), and the other experimental conditions were the same as those in Example 1. Compared with Example 1, Y2O3 was more evenly distributed in the AlON / Y2O3 mixed powder after ball milling, and the locally enriched Y2O3 was composed of particles with smaller particle sizes and fewer numbers (see Figure 3 (c) and (d)). The wavelength range of the prepared AlON transparent transmittance ≥ 80% is 370-4200nm, the maximum infrared transmittance is 83.3%, and the transmittance at 400nm is 80.4%. Figure 4 Pores can be observed in the fracture morphology of the ceramics obtained by this method ( Figure 5 (b)), the α-Al2O3 content is low during the heating process ( Figure 6 ), no local particle aggregation / coarsening phenomenon was observed in the early and middle stages of sintering ( Figure 7 ), the densification process is faster during the heating stage ( Figure 8 ), the relative density of the ceramic after heat preservation sintering is 99.74%.
[0066] Comparative Example 2
[0067] Comparative Example 2: The method of Example 1 is followed, except that the Y2O3 sintering aid used is a pure phase micron-sized lamellar powder ( Figure 1 (a) and (d)). Y2O3 has serious local enrichment in the AlON / Y2O3 mixed powder after ball milling ( Figure 3(e) and (f)). The transmittance curves of the prepared AlON transparent ceramics are shown in Figure 4 The transmittance range is relatively narrow, with a transmittance of ≥80% only in the 2440-4150nm band, a maximum transmittance of 82.8%, and a transmittance of 66.9% at 400nm. A large number of large-sized pores can be seen in the fracture morphology of the ceramic obtained by this method ( Figure 5 (c)), the α-Al2O3 content is high during the heating process ( Figure 6 ), resulting in localized particle aggregation / coarsening in the early stage of sintering ( Figure 7 ), the densification process is slow in the early and middle stages of sintering ( Figure 8 ), and the relative density of the sample after heat preservation sintering is also low (99.41%).
Claims
1. A rapid pressureless sintering method for preparing wide-band high-transmittance AlON ceramics, characterized in that: The Y2O3 raw material powder and the AlON raw material powder are ball-milled and mixed, and then dried and granulated to obtain the AlON / Y2O3 mixed powder; then the AlON / Y2O3 mixed powder is preformed by unidirectional pressure, and then cold isostatically pressed to obtain a green body; finally, the green body is pressurelessly sintered in a nitrogen atmosphere to obtain a wide-band high-transmittance AlON transparent ceramic, wherein: The Y2O3 powder in the AlON / Y2O3 mixed powder is uniformly distributed in the mixed powder in the form of single particles and clusters consisting of 2 to 5 and 6 to 60 single particles. The mass of the Y2O3 powder in the cluster form consisting of 6 to 60 single particles is 50% to 80% of the Y2O3 raw material powder.
2. The method according to claim 1, characterized in that: The primary particle size of the Y2O3 raw material powder is 20-100 nm, the primary average particle size is 30-70 nm, and the specific surface area is 20-30 m 2 / g.
3. The method according to claim 1 or 2, characterized in that: The Y2O3 raw material powder can be first ball-milled in anhydrous ethanol at a speed of 150-180 rpm for 8-14 hours using silicon nitride balls with a diameter of 3-5 mm and then mixed with AlON powder, wherein the ball-to-material ratio of the ball-milled Y2O3 raw material powder is 8-11:
1.
4. The method according to claim 1, characterized in that: The Y2O3 raw material powder can be prepared by the following method: S1: Weigh yttrium nitrate and citric acid in a molar ratio of 1:3, add 50 mL of deionized water, and stir to dissolve until a transparent solution is formed; S2: Weigh ethylene glycol in a molar ratio of 3:1 between citric acid and ethylene glycol, add it to the transparent solution obtained in S1, heat it to 70-90°C in an oil bath, and continue stirring until a viscous sol is formed; S3: The viscous sol obtained in S2 is kept in an oven at 70-90°C for 20-26 hours to form a gel; S4: heating the gel obtained in S3 to 220-250°C in a muffle furnace at a rate of 5-30°C / min and maintaining the temperature for 1-4 hours to foam and form a porous precursor; S5: Grind the porous precursor, pass it through a 50-mesh sieve, heat it to 850-950°C in a muffle furnace at a rate of 10-20°C / min and keep it at that temperature for 1-4 hours to obtain pure Y2O3 powder.
5. The method according to claim 4, characterized in that: The purity of the yttrium nitrate is ≥99.99%, the purity of the citric acid is ≥99.5%, and the purity of the ethylene glycol is ≥99%.
6. The method according to claim 1, characterized in that: The Y2O3 raw material powder and the AlON raw material powder are first ball-milled at 150-180 rpm for 12-14 h, and then ball-milled at 180-240 rpm for 16-20 h to obtain AlON / Y2O3 mixed powder. The D 50 The particle size distribution range is 0.8-1.4 μm, and the particle size distribution range is 0.05-8.0 μm, wherein the amount of Y2O3 raw material powder added is 0.2-0.4% of the mass of AlON raw material powder.
7. The method according to claim 1, characterized in that: The unidirectional press preforming is completed at 30-60 MPa, and the cold isostatic pressing is completed at 100-180 MPa.
8. The method according to claim 1, characterized in that: The heating rate of the pressureless sintering is 10-30°C / min, the sintering temperature is 1860-1900°C, and the heat preservation time is 3.5-5.5h.
9. The method according to claim 1, characterized in that: The method comprises a post-processing step of grinding and polishing the AlON transparent ceramics prepared by rapid pressureless sintering.
10. The AlON transparent ceramic prepared by the method of claim 1, characterized in that: The transmittance in the 350-4480nm band is ≥80%, the maximum transmittance is 87.5%, the transmittance at 400nm is 81.2%, and HV>17GPa.
Citation Information
Patent Citations
Low-temperature preparation method of transparent aluminum oxynitride (AlON) ceramic
CN104387081A
Method for preparing Cr-Y-O nanocluster oxide dispersion strengthening steel
CN105238986A
Preparation method and application of temperature sensitive type Y2SiO5:Eu intelligent thermal barrier coating
CN106119765A
High-performance AlON transparent ceramic and low-temperature rapid preparation method thereof
CN114538931A
Preparation method of nano yttrium oxide material
CN115838185A